2009
DOI: 10.1104/pp.109.140046
|View full text |Cite
|
Sign up to set email alerts
|

Thiamin Confers Enhanced Tolerance to Oxidative Stress in Arabidopsis

Abstract: Thiamin and thiamin pyrophosphate (TPP) are well known for their important roles in human nutrition and enzyme catalysis. In this work, we present new evidence for an additional role of these compounds in the protection of cells against oxidative damage. Arabidopsis (Arabidopsis thaliana) plants subjected to abiotic stress conditions, such as high light, cold, osmotic, salinity, and oxidative treatments, accumulated thiamin and TPP. Moreover, the accumulation of these compounds in plants subjected to oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
218
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(234 citation statements)
references
References 57 publications
11
218
1
4
Order By: Relevance
“…Several studies found that there is a strong correlation between the enzymatic antioxidant defence system and the salt tolerance of plants (Misra et al, 2006;Tunc-Ozdemir et al, 2009). The present study found that the POD and SOD activities increased with an increase in the salt concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that there is a strong correlation between the enzymatic antioxidant defence system and the salt tolerance of plants (Misra et al, 2006;Tunc-Ozdemir et al, 2009). The present study found that the POD and SOD activities increased with an increase in the salt concentration.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that HRD3A is at least important for removing the source of ROS production in plant cells, and perhaps this is the reason why the hrd3a plants showed arrested growth and died more quickly under the salt treatment condition. The chemical paraquat, an inducer of oxidative stress, can induce cell death in both plants and animals [40,41]. To determine whether paraquat can be more harmful to hrd3a mutant plants, hrd3a-1, hrd3a-2, and WT seeds were plated and grown on MS medium containing 0.2 µM paraquat.…”
Section: Ros Is Involved In the Erad-related Plant Salt Response Pathwaymentioning
confidence: 99%
“…As a signaling molecule, NO is believed to be one of the first antioxidants during early evolution which can up-regulate antioxidants (Beligni and Lamattina 2002) and indirectly mediate H 2 O 2 level in the cascade of events leading to alterations of antioxidant gene expression (Leshem 1996). A great variety of abiotic stresses including drought, salinity, ultraviolet light, air pollutants and heavy metals cause damage to plants, either directly or indirectly through reactive oxygen species (ROS) formation (Tunc-Ozdemir et al 2009), such as superoxide anion (O 2 -) and hydroxyl (OH) radicals, hydrogen peroxide (H 2 O 2 ), and singlet oxygen ( 1 O 2 ). Two mechanisms are proposed by which NO might abate oxidative stress.…”
Section: Role Of No In Abiotic Stress Responsesmentioning
confidence: 99%